BIOENERGY VILLAGES – A BLUEPRINT FOR RURAL ENERGY SUPPLY? - KÖNIG, Andreas; JENSSEN, Till (Journal of Environmental Management and Tourism, 2010)
Many European municipalities develop energy supply concepts based on renewable energies to reduce energy related greenhouse gas emissions and stimulate regional and rural economies. Improvement of security of supply using regional energy sources is an additional motivation for renewable energy investments. An increasing number of municipalities in the rural environment seek to meet all their energy demands with biomass. This article provides a system analysis of “Bioenergy Villages”, balancing costs and CO2 reduction of a rural model village in Germany. The results show that a 100 % energy supply based on biomass potentials within the boundaries of the municipality is technically possible but not reasonable with respect to land-use competition and costs of energy supply. The production of transport fuels based on energy crops (rape seed) leads to significant increase of costs and is dependent on a considerable raw material import from outside the municipality. Heat and power demand can be covered with biomass without an important increase in competition to other land use patterns and to relatively low costs. Thus utilization of biomass for heat and power production leads to a cost efficient CO2 reduction whereas the transportation fuel production comes along with relatively high reduction costs and depletion of regional biomass and land area potentials.